2015
DOI: 10.1088/1367-2630/17/3/035007
|View full text |Cite
|
Sign up to set email alerts
|

Reactive collisions in confined geometries

Abstract: We consider low energy threshold reactive collisions of particles interacting via a van der Waals potential at long range in the presence of external confinement and give analytic formulas for the confinement modified scattering in such circumstances. The reaction process is described in terms of the short range reaction probability. Quantum defect theory is used to express elastic and inelastic or reaction collision rates analytically in terms of two dimensionless parameters representing phase and reactivity.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…By solving the Schrödinger equation with the pseudopotential (6) and boundary conditions (9), we obtain [21,47] …”
Section: Atomic Scattering In a Quasi-1d Waveguidementioning
confidence: 99%
“…By solving the Schrödinger equation with the pseudopotential (6) and boundary conditions (9), we obtain [21,47] …”
Section: Atomic Scattering In a Quasi-1d Waveguidementioning
confidence: 99%
“…To investigate chemical reactions between cold molecules, optical lattices are a convenient testbed as they allow for either isolating the molecules from each other or letting them collide. In addition optical lattices offer the possibility to control the dimensionality of the scattering process and to tune the interaction [35][36][37][38] . Based on this approach, it has been shown that strong inelastic collisions induce correlations and can inhibit particle loss in a molecular sample, a manifestation of the quantum Zeno effect 15,34 .In this work we present the first measurements on ultracold collisions of metastable triplet molecules that are internally in their lowest energy state.…”
mentioning
confidence: 99%
“…The description changes when reducing the dimensionality of the scattering process 35,48 . Generally, a system enters the quasi-1D regime for large trap aspect ratios ωx, ωy ωz and low enough collision energies Ecol < 2 ωx,y.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ultracold high phase-space-density gases of polar molecules in their absolute rovibrational ground state have already been produced [41][42][43][44][45] and allowed for groundbreaking experiments on controlled chemical reactions [46][47][48][49]. An unprecedented control over ultracold molecular collisions has been achieved by selecting molecules' internal states and by tuning dipolar collisions with an external electric field in a reduced dimensionality [50][51][52][53][54][55][56]. Ultracold polar molecules have been also produced in an optical lattice [57], and dipolar spin-exchange interactions between lattice-confined polar molecules have been observed [58], opening the way towards quantum simulations with molecules [59].…”
Section: Introductionmentioning
confidence: 99%